The Effect of Work Motivation, Work Environment, and Communication on Employee Performance at SMP Bonavita Tangerang - Herryadi Herryadi; Pujiarti Pujiarti (eCo-Fin, 2024)
is study was conducted to analyze and determine the influence of work motivation, work environment, and communication on employee performance at Bonavita Tangerang Junior High School. This study aims to understand how work motivation, work environment, and communication, both individually and together, affect employee performance. This study uses a quantitative approach, data collection through questionnaires and then analyzed using the SPSS version 25 program. The results of regression analysis show that work motivation, work environment, and communication have a positive and significant influence on employee performance. Work motivation affects performance by 58.7%, work environment by 80.9%, and communication by 67.8%. Overall, the influence of these three variables on employee performance is stronger than other factors. Based on the results of statistical analysis, the calculated f-value for the independent variables that were analyzed simultaneously was 51.100, which exceeded the table f-value of 8.594. These findings indicate that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that work motivation, work environment, and communication have a positive and significant effect on employee performance at Bonavita Tangerang Junior High School.